The X tax in the world economy - David F. Bradford (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper considers the treatment of multinational business in the system known as an X Tax. The focus is on the choice between origin and destination treatments of transborder transactions. The destination-principle approach sidesteps the transferpricing problem. It remains in the origin-principle approach, which, however, presents fewer challenges of monitoring the imports, obviates the ?tourism problem? whereby people can reduce their taxes by consuming in a low-tax jurisdiction and avoids transition effects associated with introduction of the tax and subsequent tax rate changes. The paper suggests special rules for transborder transactions between related parties to deal with the transfer-pricing problem.
Keywords: H25; H87; H20; 330; Transferpreis; Unternehmensbesteuerung; Vereinigte Staaten; Welt